Communities and Technologies 2003
DOI: 10.1007/978-94-017-0115-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia Fliers: Information Sharing With Digital Community Bulletin Boards

Abstract: Abstract. Community poster boards serve an important community building function. Posted fliers advertise services, events and people's interests, and invite community members to communicate, participate, interact and transact. In this paper we describe the design, development and deployment of several large screen, digital community poster boards, the Plasma Posters, within our organization. We present our motivation, two fieldwork studies of online and offline information sharing, and design guidelines deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 21 publications
7
62
0
Order By: Relevance
“…As we already discussed in the introduction, Churchill et al [8] found that people needed constant encouragement and demonstration to interact with the public display. Similarly, Agamanolis [2] has noted that half the battle in designing an interactive situated or public display is designing how the display will invite that interaction.…”
Section: Enticing Interaction With Public Displaymentioning
confidence: 99%
“…As we already discussed in the introduction, Churchill et al [8] found that people needed constant encouragement and demonstration to interact with the public display. Similarly, Agamanolis [2] has noted that half the battle in designing an interactive situated or public display is designing how the display will invite that interaction.…”
Section: Enticing Interaction With Public Displaymentioning
confidence: 99%
“…Taylor et al [16] looked at community notice boards in a rural village to inform the design of a digital version. Churchill et al [4] looked at community notice boards in an urban area and in their own workspace to inform the design of their Plasma Poster Network, a system that enhances the chance to encounter interaction and awareness of different workgroups' activities. Huang et al [8] conducted a field study to analyze various paper and digital displays and their actual placement, as well as how much people actually look at them.…”
Section: Related Workmentioning
confidence: 99%
“…The use of large displays for group interaction has been studied in two main areas: 1) supporting group awareness and collaboration in the workplace [3,20,28] and 2) supporting social interaction and media sharing in (semi)public settings [17]. Examples include coordination of small groups in the medical domain [32], the use of large-displays for large-scale collaboration in NASA control rooms [15,29] and in classrooms [8].…”
Section: Introductionmentioning
confidence: 99%